Analisis Kesalahan Siswa Menggunakan Tahapan Kastolan Dalam Menyelesaikan Soal Cerita - Patrisius Bauk; Oktovianus Mamoh; Justin Eduardo Simarmata (Pendidikan Matematika UNIMOR, 2022)
The purpose of this research was to determine the types and factors of errors made by grade VII students of SMP St. Yosef Maubesi in solving story problems on the subject of operations in algebraic forms. The research method used is descriptive qualitative. The research subjects were students of class VII SMP St. Yosef Maubesi. Data collection techniques used are tests, interviews, and documentation. The instruments in this research were the researcher, the test sheet, and the interview guide. Based on the results, it was found that conceptual errors were made by subjects 1, 2, and 3 on the questions being worked on. The cause of the subject making mistakes is that students do not understand the meaning of the question and students do not know the formula used. Procedural errors were made by subjects 1, 2, and 3 on the questions being worked on. The cause of the subject making mistakes is that students are not careful in the work process and technical errors are made by subjects 1, 2, and 3 on the questions being worked on. The causes of the subject making mistakes are: students are in a hurry to write the ending and do not understand the calculation process and students do not re-check the results of their work.